2015
DOI: 10.1007/s00216-015-8627-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic-based retention time predictions of endogenous steroids in comprehensive two-dimensional gas chromatography

Abstract: This work evaluates the application of a thermodynamic model to comprehensive two-dimensional gas chromatography (GC × GC) coupled with time-of-flight mass spectrometry for anabolic agent investigation. Doping control deals with hundreds of drugs that are prohibited in sports. Drug discovery in biological matrices is a challenging task that requires powerful tools when one is faced with the rapidly changing designer drug landscape. In this work, a thermodynamic model developed for the prediction of both primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…McGinitie et al worked with a single standard mixture of alkanes, alcohols, and ketones for which average errors of 0.64 % for 1 t r and 2.22 % for 2 t r predictions were obtained [17]. Silva et al on the other hand reported average retention time errors of 3.6 s for 1 D and 0.2 s for 2 D for endogenous steroids [82]. Regardless of the chemical composition of the used samples, most of the published works reported higher modeling errors for the 2 t r predictions in comparison with those of the 1 t r .…”
Section: Performance Of Thermodynamic-based Modelsmentioning
confidence: 99%
“…McGinitie et al worked with a single standard mixture of alkanes, alcohols, and ketones for which average errors of 0.64 % for 1 t r and 2.22 % for 2 t r predictions were obtained [17]. Silva et al on the other hand reported average retention time errors of 3.6 s for 1 D and 0.2 s for 2 D for endogenous steroids [82]. Regardless of the chemical composition of the used samples, most of the published works reported higher modeling errors for the 2 t r predictions in comparison with those of the 1 t r .…”
Section: Performance Of Thermodynamic-based Modelsmentioning
confidence: 99%
“…GCxGC predicted retention times for steroids have been modelled based on thermodynamic properties. [43] Silva et al reported the advantage of this is that these thermodynamic models are independent of the operating conditions and that the use would aid in the identification of unknowns, as the authors suggest this is still a limiting factor in GCxGC due to the "thousands of peaks". Following on from previous work, this was based on the use of a thermally modulated system.…”
Section: S1 -Anabolic Agentsmentioning
confidence: 99%
“…For instance, maximum 2 t r deviations of 1.2 and 0.4 s along with a 2 t r relative deviation of 7% were reported in the literature for cryogenically modulated systems. 9,11,13 Contrastingly, average 2 t r relative errors (REs) of 2.22 and 2.09% were reported for flow-modulated systems. 10,18 The lack of direct user pressure control in cryogenically modulated systems, except for the pressure control at the inlet, was argued to be one of the main contributors to this difference.…”
mentioning
confidence: 93%
“…On the other hand, they help shift the analytical chemist’s focus to the more onerous, tedious, and time-consuming data-processing step. In this respect, considerable modeling efforts were dedicated to studying the GC × GC separation mechanisms, most of which have patently focused on modeling the thermodynamics of the separation. …”
mentioning
confidence: 99%
See 1 more Smart Citation